Seawater carbonate chemistry and competition between soft coral (Xenia) and hard coral (Stylophora pistillata) - Ana C Grillo; Susana Marcela Simancas-Giraldo; Nico Steinel; Cybelle M Longhini; Marcelo Oliveira Soares; Sonia Bejarano; G O Longo (PANGAEA, 2025)
We conducted a 28-day laboratory orthogonal experiment to test if acidification (950 μatm pCO2) and moderate to high nitrate enrichment (4 and 8 μmolL-1) negatively affect the hard coral Stylophora pistillata while physically competing with the soft coral Xenia spp. We measured photosynthetic efficiency (PE) in hard corals and growth rate, Symbiodiniaceae density, and chlorophyll-a concentration in both hard and soft corals as proxies for their condition and responses to competition. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from James Cook University (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-16.